APBD STRUCTURE ON REGIONAL FINANCE AND ECONOMIC GROWTH IN NORTH SUMATRA - Panjaitan, Indy Tiffany; Ramadhani, Nissa Nur; Ritonga, Syaiful Abdi (Universitas Negeri Medan, 2023)
This study aims to evaluate whether the local government of Medan has used APBD economically, efficiently, and effectively (value for money), then conducted a budget analysis on the expenditure of the area among others to find out the occurrence of Shopping Variance, against the difference or discrepancy between the realization of expendits and the budget. To know the growth rate of purchases, the development of expenditures from year to year, to know the Commercial compatibility or balance between expenditure in the function of the budget as a tool of distribution, allocation and stabilization carried out by the Local Government. To measure the level of efficiency of the use of the government budget of the City of Medan in realising regional purchases. The data collected and used in this research are secondary data obtained from the official document – the Budget Realization Report relating to the performance of the Budget of the Government of the City of Medan for the year 2016 to 2020, which was acquired from the Financial and Regional Asset Management Agency (BPKAD) of the Town of Medan. The results of this study found that the Local Government Shopping Variance is said to be efficient and effective because on the realization of spending does not exceed the budget. Government Shopping growth in the city of Medan in 2016 to 2020 from year to year has increased, except in 2020 has decreased. Noting that performance in compiling estimates is growing every year. Government Shopping Efficiency of the City of Medan in 2016 to 2020 is said to be doing well spending budget savings and efficiency of less than 100%, this can be seen from an average percentage of 78% with the criteria of compatibility.